The wars of the Romans: a critical edition and translation of De Armis Romanis - Gentili, Alberico (Oxford University Press, 2011)
A project of the Institite for International Law and Justice at New York University School of Law - t.p. - Bibliography: p. [367]-371. - Includes indexes. - Translated from the Latin